Práticas agrícolas e degradação hídrica em Adustina - BA : propostas de educação ambiental no ensino fundamental II - Andrade, Vanessa de Jesus (2023)
The agricultural practices developed in Brazil have caused various forms of environmental degradation, which lead to the difficulty of using rural spaces in several Brazilian states. The research presented here aims to analyze the environmental degradation of the Real River from the practice of agriculture developed in the municipality of Adustina-BA. To this end, specific objectives were outlined, which include: analyzing the use and occupation of the land of the communities bathed by the river; understand the production model of family farming with their respective techniques and develop methodological practices of environmental education with elementary school students. The key question for the research is: has agriculture in the municipality of Adustina-BA contributed to the process of environmental degradation of the Real River? It was listed as the main hypothesis that the environmental degradation of the Real River in the municipality has been intensified by the practice of family farming. To carry out the research, a hypothetical-deductive methodology was developed, Being as for its explanatory objective with qualitative approach, having as procedures the bibliographic survey and fieldwork with the systematic observation through interviews, elaboration of mapping, development of pedagogical practices and photographic records. It was sought to characterize the pedagogical stages in four steps, which allowed the subsequent data collection, which were discussed. By perceiving then, the influence that agriculture has in the municipality as socioeconomic and environmental aspects, the research allowed a greater knowledge of the reality in the face of socio-environmental impacts, enabling society to acquire knowledge of reality and mobilizing for behavior change through awareness promoted with the performance of Environmental Education practices, with an extension of academic research to the social sphere. Thus, an interdisciplinary perspective is presented that permeates from the theoretical and field survey, emphasizing the relationship between environment and society, to the appointment of the intervention proposal, through Environmental Education. The research had the elaboration of a technical product and in this proposal was elaborated a didactic game that reached the target audience of students of Elementary School II, which dialogued on the recurrent curricular themes with interdisciplinarity. Thus, this was the didactic product generated as a concrete return to society. In addition, the analyses made denoted agricultural practices as influential factors in the process of environmental degradation in the landscape, highlighting deforestation, silting and contamination resulting from the planting of corn and its technological packages, compromising the human supply. Thus, environmental education was emphasized for the formation of conscious attitudes, having a long historical process in Brazil and in the World, being fundamental to be approached in an interdisciplinary way. Therefore, the pedagogical practices carried out with the target audience of Elementary School II, were developed in this purpose, with questionnaires applied, lectures, field visit and application of the didactic game, which allowed a follow-up of the development of the students in the face of the EE process, initially identifying the problems involving agricultural practices, for later theorization of basic concepts such as the watershed, aiming at the students' understanding of the local dilemmas of the municipality.